The effect of different degree of compaction towards electrical resistivity value for cohesive soil - Abd Malik, A. K.; Madun, A.; Abu Talib, M. K.; Pakir, F.; Md Dan, M. F.; Abu Bakar, N. (2023)
Electrical resistivity is a non-destructive method used to measure the resistivity of ground properties, which is related to soil properties such as porosity and degree of saturation, as described in Archie's law. In road construction, soil compaction is a crucial process that requires quick quality assessment. Traditional methods, such as sand replacement tests, are timeconsuming, limited in coverage, and labour-intensive. Therefore, incorporating electrical resistivity techniques on the current quality control practices may significantly improve efficiency. To achieve this, it is essential to establish the relationship between soil density, moisture content, and electrical resistivity. This study focuses on industrial and natural soil samples compacted using standard proctor moulds using 2.5 kg and 4.5 kg hammers. Resistivity measurements were conducted using the Miller 400A device using Wenner array and 1 cm electrode spacing. The impact of different compaction degrees on electrical resistivity values were compared for the two soil samples. The findings showed that soil dry density increased with the increment of water content until it reached maximum dry density. However, as water content continued to increase, the dry density decreased. Based on the results, electrical resistivity was higher at low water content but reduced with the increments of water contents. The resistivity value for industrial soil decreased from 164 to 12 Ohm.m and 200 to 13 Ohm.m. For natural soil the resistivity value decreased from 45 to 9 Ohm.m and 126 to 11 Ohm.m. The comparison of electrical resistivity values between the two different compaction methods indicated the moisture content limited the capability of the electrical resistivity method to identify the compaction effect in the proctor soil testing. This study demonstrates the potential applicability of electrical resistivity techniques in assessing soil compaction